PENGARUH MACAM PUPUK KANDANG DAN UMUR PANEN TERHADAP PRODUKSI RUMPUT GAJAH (Pennisetum Purpureum) - Ginting, Harianto Ginting (Agroprimatech, 2024)
The aim of this study is to ascertain the impact of different forms of manure on the production of elephant grass, as well as the relationship between the types of manure and harvest age on the production of elephant grass. The study was conducted at Tjut Nyak Dhien University's experimental field in the Faculty of Agriculture and Animal Husbandry in Medan. The study was conducted between February and May of 2023. A Factorial Randomized Group Design (RAK) with two treatment factors was employed in the study. First, there are four treatment levels represented by the symbol P (planting medium): P0 (control); P1 (chicken manure); P2 (cow manure); and P3 (goat manure). Harvest Age, represented by the symbol (W), is the second component. It is divided into two treatment levels: W1 (30 DAP) and W2 (40 HSP). The study's findings demonstrated that the number of tillers and wet weight were significantly impacted by the various manure treatment methods. The plant height was significantly affected by the harvest age treatment. The interaction of the two treatments had a very significant effect on the number of tillers and a significant effect on the wet weight. The highest production was obtained in the P3W1 treatment (goat manure; harvest age 30 DAP).In the P3W1 treatment (goat manure; harvest age 30 DAP), the highest output was achieved. Goat manure application had the greatest effect on the plant metrics of fresh weight and tiller count. Harvesting following leveling at intervals of forty days has the greatest effect on plant height metrics. The parameters of the number of tillers and weight wet with P3W1 treatment (goat manure; harvest age 30 days) are most influenced by the combination of manure types and harvest age.